Investigation for Adrenal diseases- An Overview (Journal of Medicine, 2025)
Adrenal diseases encompass a wide range of disorders involving hormone excess or deficiency, adrenal masses, and congenital anomalies. Accurate and timely diagnosis is crucial to guide effective management and avoid potentially life-threatening outcomes.This review provides a comprehensive overview of current investigative approaches for adrenal disorders, integrating recent advancements and established methodologies. It highlights the interpretation of hormonal assays for conditions such as primary adrenal insufficiency (Addison’s disease), Cushing’s syndrome, primary hyperaldosteronism (Conn’s syndrome), Pheochromocytoma/paraganglioma (PCC/PGL) and congenital adrenal hyperplasia (CAH). The utility of dynamic endocrine tests, biochemical markers, and imaging modalities including CT, MRI, and nuclear imaging is discussed. Additionally, the role of genetic testing and emerging diagnostic algorithms is outlined. By summarizing practical approaches and updates in diagnostic strategies, this review aims to aid clinicians in the systematic evaluation of adrenal pathologies, ensuring accurate diagnosis and individualized patient care.J MEDICINE 2025; 26(2): 163-170